Narrativizing Trauma: A Way of Anticipating Peace and Solidarity in Dhurba Chandra Gautam’s “The Conclusion” - Pokharel, Badri Prasad (The Saraswati Review, 2024)
This article analyzes Dhrub Chandra Gautam’s story “The Conclusion” by applying Cathy Caruth’s psychological trauma and Dominick LaCapra’s middle voice. “The Conclusion” is written on the periphery of Nepal’s ten year long Maoist insurgency in which more than seventeen thousand people lost their lives and millions of others were badly affected and displaced from their own home towns or villages. Those who witnessed the horrible past have written the narratives as their testimonies with the help of imaginative characters who better present their trauma and anticipate for long lasting peace and solidarity. The narrator in this story has narrativized the horrible consequences of the war, and he/she has depicted the incidents objectively not aligning to any warring groups. Narrating the testimony of the war neutrally would enable both warring groups to accept it as their own testimony which would ultimately make them feel relief.